EFEKTIVITAS PROGRAM PERSONAL SHOPPER PAMELA SEBAGAI MEDIA DIGITAL MARKETING UNTUK MENDUKUNG PENJUALAN DI PAKUWON MALL SURABAYA - Ramadhani, Lailani Fitrah (The Commercium, 2022)
The Covid-19 Pandemic has made people's lifestyles tend to avoid crowds such as shopping centers (malls). One of the malls affected is Pakuwon Mall Surabaya. One of Pakuwon Mall Surabaya's efforts in dealing with this is by doing digital marketing through a Personal Shopper program called Pamela. The purpose of this research is to find out and identify the effectiveness of Pamela's Personal Shopper program as a digital marketing media at Pakuwon Mall Surabaya during the Covid-19 pandemic era. This research method uses quantitative research. The sample used is Pakuwon Mall visitors who know about the Pamela Personal Shopper program, both those who have used it and those who have never used it, totaling 100 consumers. The results of the study based on the AIDA concept, Pamela obtained a mean value of the attention dimension of 4.33 which was in the very effective category, the interest dimension obtained a mean of 4.21 was in the very effective category, the desire dimension obtained a mean value of 4.13 was in the effective category. and the action dimension has a mean of 3.88 which is in the effective category. Overall obtaining a mean of 4.14 and is in the effective category. The effectiveness of Pamela's Personal Shopper in making sales is 77.7%. The results of hypothesis testing using one sample t test show that digital marketing owned by Pakuwon Mall Surabaya, namely through Pamela, is significantly effective in making sales. Keywords: Effectiveness, Digital Marketing, Increased Sales